Nutrição potássica em soqueira de cana-de-açúcar colhida sem queima - Almeida, Hilário Júnior de [UNESP] (2013)
The elimination of straw burning of sugarcane (Saccharum spp.) propitiates the mulch left in the field, promoting improvement of soil fertility and can reduce the use of potash fertilizers. This study aimed to evaluate the response of first and second sugarcane ratoon cultivated in conservative management system, the potassium levels, in Red-yellow latosol (Hapludox) (LVAD) and Red-yellow Argisol Eutrophic (PVAe). Two experiments, one in LVAD (variety SP81-3250) and another in PVAe (variety RB855453) were developed. The treatments consisted of doses of 32,5; 65; 130 and 195 kg ha-1 of K2O, in the form of potassium chloride, besides the control (without potassic fertilizer), arranged in a randomized block design with five replications. The plots that received the treatments in the first ratoon were once again treated with the same doses in the second ratoon. The plots that received the treatments in the first ratoon were once again treated with the same doses in the second ratoon. Were applied 100 kg ha-1 of nitrogen in the form of urea and 30 kg ha-1 of P2O5 in the form of triple superphosphate. The fertilizers were applied to the side of the line of ratoon from sugarcane, without incorporation in each year of cultivation. Were evaluated the biometric variables (height, tiller number and diameter); potassium contents in soil, straw and plant, production and quality of the culms in two seasons (2010/2011 and 2011/2012). Potassium fertilization resulted in higher contents of nutrients in the soil and the plant, reflecting gains in the production of culms, both the first as the second sugarcane ratoon in both soils evaluated. The dose of 65 kg ha-1 of K2O is associated with 97 and 98% of the maximum production at the first ratoon, while, in the second ratoon this dose represents 90 and 95% of the maximum production respectively for the LVAd and PVAd